Bi‐Directional Electrocatalytic Detection of Dopamine at an Electrode Modified with Ferrocene‐Filled Carbon Nanotube Peapods. Issue 9 (27th August 2013) - Cheng, Huiming; Guan, Lunhui; Shi, Zujin; Zhu, Zhiwei; Gu, Zhennan; Li, Meixian
Abstract A glassy carbon electrode (GCE) was modified with nanopeapods formed by ferrocene filled single‐walled carbon nanotubes (Fc@SWNTs). The modified electrode showed bi‐directional electrocatalysis toward dopamine (DA), which suggested a synergistic effect of ferrocene and carbon nanotubes. Bi‐directional detection of DA was realized based on the modified electrode.